The Effects of Financial Information Symmetry on Conflict Resolution: An Experiment in the Context of Labor Negotiations. - Elias, Nabil (The Accounting Review, 1990)
Abstract Deals with the effects of financial information disclosure to union negotiators on the resolution of industrial conflict. Theoretical development of hypotheses; Pre-negotiation expectations and perceptions.